Görünür Bölgede Işık Uygulamasının Hasat Sonrası Domateslerin Raf Ömrü Ve Kalitesi Üzerine Etkisinin İncelenmesi - Akın, Halime Esin (Fen Bilimleri Enstitüsü, 2016)
Son yıllarda meyve-sebzelerin saklamanmasında raf ömrünün uzatılmasının yanı sıra ürünün fitobesin içeriği ve tekstür gibi duyusal özelliklerinin de mümkün olduğunca korunduğu yaklaşımlar oldukça önem kazanmaktadır. Buzdolabında meyve-sebzelerin saklanmasında genellikle, sıcaklık ve nem kontrol edilirken; ışık çoğunlukla göz ardı edilmektedir. Buzdolaplarında raf ömrünü uzatma, ürün tazeliğini ve besin kalitesini koruma amaçlı dikkat edilmesi gereken yeni teknolojiler uygulama alanı bulmaktadır. Bunlar arasında başlıca görünür bölgede LED (light emitting diode) uygulamaları yer almaktadır. Bu çalışmada, +4°C sıcaklıkta %90 bağıl nem koşullarında saklanan domates örneklerine görünür bölgede mavi LED ışık uygulamasının ürünün fitobesin içeriği, stoma çapı, ağırlık kaybı ve duyusal kalitesi üzerine etkisi incelenmiştir. Bu amaçla, testlerde 460 nm dalga boyunda mavi LED kullanılmıştır. Öncelikle karanlıkta depolanan ve 24 saat çalışan mavi LED altında raf ömrü boyunca saklanan domates örnekleri arasındaki fitobesin içeriği ve duyusal kalite karşılaştırılmıştır. 24 saat mavi LED uygulamasının domateslerin C vitamini, ve kabuk rengi gibi özelliklerin iyileşmesini ve depolama süresince C vitamini ve kabuk renginin yanısıra likopen içeriğinin de daha iyi korunmasını sağladığı görülmüştür. Her ne kadar, 24 saat mavi ışık uygulamasında ürünün fitobesin içeriğinin depolama süresince daha iyi korunduğu görülmüş olsa da, ürünün raf ömründe bir farklılık tespit edilmemiştir. İkinci aşamada, 24 saat mavi LED uygulaması ile 12 saat mavi LED uygulaması karşılaştırılmıştır. C vitamini miktarı, kabuk rengi değerlerinin her iki grupta da benzer seyrettiği görülmüştür. Ayrıca, likopen içeriğinin 12 saat mavi LED uygulaması yapılmış ürünlerde daha iyi korunması nedeniyle ışık uygulamasının fotoperiyot süresinin 12 saat olmasına karar verilmiştir. Bu sayede, enerji tasarrufu da sağlanmıştır. Mavi ışık uygulamasının periyotlu ya da sürekli çalışıyor olmasının da domateslerin raf ömründe bir farklılık oluşturmadığı görülmüştür. Duyusal analizlerde, panelistlerce raf ömrünün belirlenmesinde en önemli kalite kriterinin doku değişimi olduğu yorumu yapılmıştır. Ağırlık kayıplarının her iki testte de 24 saat mavi LED uygulamasında daha yüksek seyrettiği görülmüştür. Bu durumun nedeni, mavi LED ışık altında ürün stomalarının uyarılması sonucu olabileceği yorumu yapılmıştır. Ancak, stoma görselleme çalışmalarında bu durum stoma çapı uzunluklarında istatistiksel fark yaratmazken,yine de stoma çaplarının ortalama uzunluklarının depolama süresince 24 saat mavi LED ışık altında saklanan örneklerde daha yüksek olduğu görülmüştür. Sonuç olarak, bu çalışma kapsamında görünür bölgede mavi LED ışık uygulamasının, +4°C ve %90 bağıl nem koşullarında depolanan domateslerin fitobesin içeriğinde (özellikle C vitamini ve likopen miktarı açısından) iyileştirmeler sağladığı görülmüştür.

In recent years, the studies about extending the storage life also with preventing fitonutrition content and sensory qualities of fruits and vegetables are very popular while post harvest storage. In most studies about fresh produce in refrigerators while postharvest storage time, although temperature and humudity are controlled, the light effect is mostly ignored. Novel technologies have found the area of application about prolonging the storage life, preventing the fitonutrition quality and freshness of foods. LED applications in visible region are also located among them. First of all, for this topic, the most appropriate light sources to the fruits and vegetables were researched. In literature, it is seen that there are 4 types of lambs basically that are used in pre- and postharvest period of fruits and vegetables. These are high intensity discharge lambs, metal halogen lambs, fluorescents and LEDs. However it is also seen that high intensity discharge lambs and metal halogen lambs are used mostly in greenhouses mostly for hydroponically growing plant systems because of their large sizes. Fluorescents and LEDs can be used both in preharvest plant growing systems and also to improve quality parameters of freshproducts while postharvest period as well. However since they have bigger sizes and irradiate light with a broad spectrum, it is not preferred to use fluorescent lambs in this study. In this study, LEDs are selected to use in visible spectrum, which irradiate blue coloured light at the wavelength of 460 nm. LEDs are a semi-conducted light supply that irradiate in visible light spectrum. They can radiate monocromattically in a narrow light spectrum. With this feature, they can radiate only the necessary light spectrum for plants. The average life of LEDs are 100.000 hours, so it is approximately 11,5 years. They are very long-stable. The other adventages of LEDs are that they spend less energy than the other lambs, have less small sizes, are easily mountable, can radiate linear light in a specific wavelength and also are cheaper than the other types of lambs. With these adventages, it is seen in the literature that they are becoming more popular to use in food storage systems. They do not give any harm to the fresh produce, since they do not radiate heat directly. So, they are also very advantageous to use in food storage systems which they should be cold. In addition, with LED control systems, the brightness and photoperiod of light could beadjusted manually or through computer systems. In this study, the effect of LED application which irradiate blue colour in visible spectrum to the fitonutrition content and sensory qualities of tomatoes at +4°C temperature, %90 relative humidity conditions were determined. The studies regarding to the effect of visible light on the products are mostly about green vegetables. In these studies, the effect of light was not determined exactly. However, the increase of vitamin C content was supposed to be contiunity of the photosynthesis reactions in post harvest storage period (photo-energetic effect). This study was done to determine the effect of visible light to products which are not green vegetables. For storage tests, tomatoes were selected which are one of the the most consumed fruits of the world. In addition, tomatoes have much nutritive value with substances such as dietary fiber, folic acid, potassium, vitamin E and C, flavanoids, carotenoids, phenolic compounds and antioxidant content. The most important quality criteria of tomatoes are the colour, texture and taste for consumer acceptance. After literature and patent applications researches, it was decided tostudy with blue and red wavelengths of visible light. Firstly, the effect of continuous blue LED light to the micronutirional and sensorical qualities of tomatoes with respect to darkness as control group. The contents of vitamin C, lycopene, total soluble solids, the changeness of outer shell colour, weight loss and sensory qualities were investigated. The initial 13,2 mg/100 vitamin C content was determined 9,0 mg/100 g in control group and 11,6 mg/100 g in samples which are treated with 24-hour blue LED after 14 days which was the last day of storage. In the storage period, the vitamin C content of 24-hour blue LED light treated samples was statistically higher than control samples. According to this, it was interpreted that the blue light treatment has a preventing effect of vitamin C. This situation proves that photosynthesis reactions are not the only way increasing vitamin C content in post harvest products. Although the effect of light to post harvest products is not exactly, it could be photo-cybernetic effect. When the effect of blue LED application on lycopene content of tomatoes were investigated; it was obviously seen that the lycopene content of tomatoes which are treated with 24-hour LED application was prevented better. In addition the lycopene content of 24-hour LED treated samples were increased until the second day of storage period. According to this, lycopene accumulation was also triggered by 24- hour blue LED light. Similarly, the outer shell colour of the tomatoes which are treated with 24-hour blue LED was more reddish than the products which were stored in the darkness. Tomatoe is a climacteric fruit, as known. Therefore maturing of tomatoes continues also in the darkness. For this reason, the redness of the outer colour of the products increased in first two days which were stored even in the darkness. However, this increase was less than the products which were stored under 24-hour blue LED light. In addition, there was not any regression between lycopene changeness and outer colour changeness in storage time period.Also, °Brix values of the tomatoes which were stored under 24-hour blue LED light were higher than control group samples. This stiuation illustrates that the sweetness of tomatoes which were treated with blue light was better in longer time of storage. In addition, on blue LED light application, the average % weight loss of productswas higher than control samples. The weight loss of samples at the last day of storage which were treated and untreated with blue LED light were % 1,40 and %1,08 respectively. The overall quality values of tomatoes in sensory analysis were quite similar, so the weight loss differences of samples did not create any difference on overall quality determination in sensory analysis. In addition in stoma visualization studies, it is also seen that the average stoma diameters were being bigger during storage in the samples that are treated with 24 hour blue LED than darkness. However the difference between these two groups and the 14-day changeness are not found important statistically. The light dose and intensity are very important to preventlight dammage on product. Therefore, in the second part of this study, LED light application time was selected as 12-hour period, which is a common photoperiod time of short-day, long-day and day-notral plants. In this situation, energy saving was targeted while selecting 12- hour application rather than 24-hour. The quality of products which were stored at the same conditions (as temprature and relative humudity) with previous, were treated with 12-hour blue LED light application and were compared with 24-hour LED blue LED light application. Among the situations of 12-hour and 24-hour blue LED light applications, there were no important differences on vitamin C content, total soluble solids, outer colour and sensory analysis results. Although, there were no any difference on lycopene contents among groups in the first 7 days of storage, at the end of the storage time period on the 14.day, the lycopene content of products which were stored under 12-hour LED light were statistically higher. At the end of the storage time period the lycopene contents of products were 18,6 mg/100 g and 19,6 mg/100 g which were treated with 24-hour and 12-hour blue LED, respectively, while the initial lycopene content of groups were 35,4 mg/100g. The average % weight loss of products which were treated with 24-hour LED light was significantly higher than samples treated with 12-hour LED application. The weight loss of samples which were treated with 24-hour and 12-hour blue LED light applications, were found % 1,69 and % 1,30 respectively. The overall quality values of tomatoes in sensory analysis were quite similar, so the weight loss differences of samples did not create any difference on overall quality determination in sensory analysis. It is also seen that the average stoma diameters were being bigger during storage in the samples that are treated with 24-hour blue LED than 12-hour blue LED in stoma visualization studies. Since more light application trigger more weight loss, the average diameter of stomat and weight loss are higher in 24-hour blue LED light application. However the difference between these two groups and the 14-day changeness are not found important statistically.Finally, within this study, it is seen that the blue LED light application has a positive effect on the fitonutritional quality (especially the point of vitamin C and lycopene content view). For the sensory quality and storage time there is not seen any difference with the samples which stored between under blue LED and in the darkness. On the continuous blue LED light application, vitamin C increased more and also was prevented more. The vitamin C content is similar within groups whichare treated with 24-hour and 12-hour blue LED light. So blue LED light application is significantly better both to increase and prevent vitamin C content of tomatoes. In the future studies, this study could be repeated with the other wavelengths and on the other fruits and vegetables in different temperature conditions. As a recommendation, to prevent light damage, the photoperiods could be done as 0,5 hour light and then 0,5 hour darkness or 1 hour light and then 1 hour darkness. It is thought that, with this situation the fitonutrient and visual quality of products would be better than continuous light treatment during photoperiod time. Therefore, in studies after this, the effects of different photoperiod times and different wavelenths of LEDs and also the effects of different flashing periods of LED applications could be studied.
Investigation Of The Effect Of Visible Light Treatment On Storage Life And Quality Parameters Of Post Harvest Tomatoes
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2016
Thesis (M.Sc.) -- İstanbul Technical University, Instıtute of Science and Technology, 2016
Keywords: Domates; Işık; Led; Saklama; Tomato; Light; Led; Storage